The contribution of "Food Hubs" in the digital age within the sustainable "agri-food" transition: A review of research in sub-Saharan Africa - (:unkn) unknown (My University, 2022)
In sub-Saharan Africa, managing the growing gap between rural supply and urban demand for good quality food products has become a serious challenge. This calls for an analysis of territorial innovation with a view to uncover an innovative model of sustainable urban supply, such as that of “Food Hubs”. To address this issue, this study questions the place they occupy in the context of digital development within scientific work, to accompany the transition to sustainable “agri-food” systems. Thus, we conducted a search on Google Scholar using the “Publish or Perish” software. The results show that, of the 105 articles published in peer-reviewed journals, there were none that focused on cities in sub-Saharan African countries. This result contrasts with the existence, as of February 2022, of ten Food Hubs in this part of the African continent. This work, therefore, recommends that case studies be carried out on these Food Hubs.
Keywords: African Research